PENGARUH IMPLEMENTASI KEBIJAKAN REFORMASI BIROKRASI TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA TENGGARA - Tumiwa, Valen; Posumah, Jhonny Hanny; Kiyai, Burhanuddin (Sam Ratulangi University, 2015)
ABSTRACT : Governance of area can walk because of existence of support various resource factorcapable to move organizational wheel of governance in order to attainment of target management of areaautonomy, including in it is Earnings Of Genuiness Area. Problem of which in questioning in thisresearch is how a far influence of Implementation Policy Of Reform Bureaucracy To Revenue OfGenuiness Area Sub-Province of Minahasa South-East